Historical trends and sources of TSP in a Sonoran desert city: Can the North America Monsoon enhance dust emissions?. (June 2015) - Moreno-Rodríguez, Verónica; Del Rio-Salas, Rafael; Adams, David K.; Ochoa-Landin, Lucas; Zepeda, Joel; Gómez-Alvarez, Agustín; Palafox-Reyes, Juan; Meza-Figueroa, Diana
Abstract: In this work, the trends of total suspended particulate matter (TSP) were analyzed during a period of 12 years (2000–2012) on the basis of meteorological parameters. The results of historical trends of TSP show that post-monsoon dust emission seems to be connected to rainfall distribution in the urban environment. Particulate matter is dominated by plagioclase, quartz, calcite, and montmorillonite phases with barium sulfate, and particles enriched in Cu, Fe, and Ce. Elemental composition and principal component analysis allow the identification of two major sources for metals incorporated in geogenic dust: cement, and traffic. Geochemical analysis of non-mobile trace elements show a similar signature as local cement brands in TSP filters, but it remains unknown if such a signature is related to cement production, erosion of buildings, or construction activities. La–Ce geochemical tracers show that geogenic dust is an important media of transportation for traffic, and cement-related contaminants. This work highlights the importance of monsoon season precipitation in dust generation in arid urban environments, and it could contribute to regional studies including the southwestern US regarding the dust emission processes and transport of pollutants across the trans-boundary. Highlights: Historical TSP trends in a Sonoran desert city. Monsoon behavior enhances dust emission in urban area. Cement and traffic sources affect geogenic dust. Lack of storm drainage system promoting dust resuspension.